Application of Emerging Teaching Models in Dental Education: A Systematic Review and Meta-Analysis - Xuefei Pang; Ling Li; Xu Liu; Yan Wang; Bo Yang (International Dental Journal)
Introduction and aims: As an experimental teaching method, emerging learning methods including problem-based learning (PBL), case-based learning, team-based learning and flipped classroom (FC) have been widely applied in dental education. This study aims to evaluate the effect of these teaching methods on dental education performance compared to traditional lecture-based learning (LBL). Methods: The search was carried out in April 2024 in PubMed, EMBASE, Web of Science, and Cochrane Library. All randomized controlled trials were included and the methodological quality assessment was based on the guidelines described in the Cochrane Handbook for Systematic Reviews, followed by a meta-analysis using Stata 14.0 software. Using standard mean deviation (SMD) and 95% confidence interval (95% CI) to determine the effectiveness of emerging teaching methods and LBL in all dental disciplines. Meta-regression was used to analyse sources of heterogeneity. Sensitivity analysis was performed to determine the stability, and Begg's analysis was used to determine whether there is publication bias. Results: A total of 29 randomized controlled trials including 3502 students were included. The results indicate that emerging educational methods have a significantly positive effect on achieving higher scores (SMD = 0.48, 95% CI = 0.34-0.62, P < .001), whether it was theoretical scores (SMD = 0.52, 95% CI = 0.32-0.72, P < .001) or skill scores (SMD = 0.45, 95% CI = 0.15-0.76, P < .001). Compared to LBL, PBL (SMD = 0.33, 95% CI = 0.01-0.65, P = .045) and FC (SMD = 0.50, 95% CI = 0.31-0.69, P < .001) can both significantly improve students’ academic performance. Conclusion: Compared to LBL, emerging educational methods (PBL, case-based learning, and FC) have significantly improved the learning effectiveness of dental students. These emerging educational methods can be advocated and popularized as routine teaching methods. Clinical Relevance: This study is the first meta-analysis of the effects of emerging teaching methods in dental education which shows great impact of emerging teaching methods on students’ development.